Mean heat transfer coefficients during the evaporation of 1,1,1,2-tetrafluoroethane (R-134a) in a plate heat exchanger - EMILA DJORDJEVIC; STEPHAN KABELAC; SLOBODAN SERBANOVIC (Journal of the Serbian Chemical Society, 2007)
In this study the transfer coefficient of evaporation heat of the refrigerant 1,1,1,2-tetrafluoroethane (R-134a) in a vertical plate heat exchanger was experimentally investigated. The results are presented as the dependancy of the mean heat transfer coefficient for the whole heat exchanger on the mean vapor quality. The influences of mass flux, heat flux and flow configuration on the heat transfer coefficient were also taken into account and a comparison with previously published experimental data and literature correlations was made.